Peculiarities of electromagnetic field oscillations of a charged particle rotating about a conductive ball; Resource-Efficient Technologies; No 3 - Mkrtchyan A. H.; Grigoryan L. Sh.; Khachatryan H. F.; Grigoryan M. L.; Sargsyan A. V. (2018, 2018)
Title screen